30-day outcomes in hip fracture patients during the COVID-19 pandemic compared to the preceding year. (15th July 2020) - Macey, Alistair R. M.; Butler, Joanna; Martin, Sean C.; Tan, Ting Yang; Leach, William J.; Jamal, Bilal
Abstract : Aims: To establish if COVID-19 has worsened outcomes in patients with AO 31 A or B type hip fractures. Methods: Retrospective analysis of prospectively collected data was performed for a five-week period from 20 March 2020 and the same time period in 2019. The primary outcome was mortality at 30 days. Secondary outcomes were COVID-19 infection, perioperative pulmonary complications, time to theatre, type of anaesthesia, operation, grade of surgeon, fracture type, postoperative intensive care admission, venous thromboembolism, dislocation, infection rates, and length of stay. Results: In all, 76 patients with hip fractures were identified in each group. All patients had 30-day follow-up. There was no difference in age, sex, American Society of Anesthesiologists (ASA) classification or residence at time of injury. However, three in each group were not fit for surgery. No significant difference was found in 30-day mortality; ten patients (13%) in 2019 and 11 patients (14%) in 2020 (p = 0.341). In the 2020 cohort, ten patients tested positive for COVID-19, two (20%) of whom died. There was no significant increase in postoperative pulmonary complications. Median time to theatre was 20 hours (interquartile range (IQR) 16 to 25) in 2019 versus 23 hours (IQR 18 to 30) in 2020 (p = 0.130). Regional anaesthesia increased from 24 (33%) cases in 2019 to 46 (63%) cases in 2020, but ten (14%) required conversion to general anaesthesia. In both groups, 53 (70%) operations were done by trainees. Hemiarthroplasty for 31 B type fractures was the most common operation. No significant difference was found for intensive care admission or 30-day venous thromboembolism, dislocation or infection, or length of stay. Conclusion: Little information exists on mortality and complications after hip fracture during the COVID-19 pandemic. At the time of writing, no other study of outcomes in the UK has been published. Cite this article: Bone Joint Open 2020;1-7:415–419.